2021
DOI: 10.3390/biom11081164
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Plasma after Remote Ischemic Conditioning in a Rhesus Monkey Ischemic Stroke Model

Abstract: Background: Animal and clinical studies have shown that remote ischemic conditioning (RIC) has protective effects for cerebral vascular diseases, with induced humoral factor changes in the peripheral blood. However, many findings are heterogeneous, perhaps due to differences in the RIC intervention schemes, enrolled populations, and sample times. This study aimed to examine the RIC-induced changes in the plasma proteome using rhesus monkey models of strokes. Methods: Two adult rhesus monkeys with autologous bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Hepponstall et al [19] have demonstrated that ApoA-I, A-II, and D levels are upregulated during the early response (15 min) and late response (24 h) phases after one-time RIC stimulation in healthy young adults. Previously, we showed that long-term use of RIC might elevate the ApoA-II level in the primate ischemic stroke model [18] . Thus, we speculated that the induced elevation of multiple apolipoproteins post-RIC might be consistent with the effects of lipid metabolism regulation by repeated RIC stimulations.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Hepponstall et al [19] have demonstrated that ApoA-I, A-II, and D levels are upregulated during the early response (15 min) and late response (24 h) phases after one-time RIC stimulation in healthy young adults. Previously, we showed that long-term use of RIC might elevate the ApoA-II level in the primate ischemic stroke model [18] . Thus, we speculated that the induced elevation of multiple apolipoproteins post-RIC might be consistent with the effects of lipid metabolism regulation by repeated RIC stimulations.…”
Section: Discussionmentioning
confidence: 69%
“…Samples were separated through a gradient of 5–31% ACN in 0.1% FA (buffer B) on the ReproSil-Pur Basic C18 column (120 mm × 150 μm, 1.9 μm particle size; Dr. Maisch HPLC GmbH, Ammerbuch, Germany) at 250 nL/min flow rate. The MS parameter setup was performed as described in our previous studies [18] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we further illustrated the underlying mechanisms that RIC could decrease stroke recurrence and white matter lesions by improving cerebral perfusion, reducing inflammation via decreasing C-reactive protein (CRP), interleukin-6 (IL-6), leukocyte count, and inhibiting the coagulation process through decreasing plasminogen activator inhibitor-1 (PAI-1) and platelet aggregation rate in patients with intracranial atherosclerotic stenosis 11. Moreover, we conducted a proteomic analysis to examine the long-term effects of RIC (5-wk consistent stimulus) in our rhesus monkey ischemic stroke model 14. The coagulation process was modulated by down-regulating levels of fibrinogen alpha chain and serpin.…”
mentioning
confidence: 99%
“…11 Moreover, we conducted a proteomic analysis to examine the long-term effects of RIC (5-wk consistent stimulus) in our rhesus monkey ischemic stroke model. 14 The coagulation process was modulated by down-regulating levels of fibrinogen alpha chain and serpin.…”
mentioning
confidence: 99%